A combination of near infrared and mid-infrared spectroscopy to improve the determination efficiency of active components in Radix Astragali. Issue 1 (February 2020) - Liu, Xuesong; Zhang, Siyu; Si, Leting; Lin, Zhonglin; Wu, Chunyan; Luan, Lianjun; Wu, Yongjiang
Radix Astragali is a popular herbal medicine in the pharmaceutical industry, and many studies have confirmed its significant medical value. The objective of this study was to achieve rapid determination of the main active components (astragaloside IV and total astragalosides) in Radix Astragali using near infrared spectroscopy, mid-infrared spectroscopy, and a combination of them. Partial least squares regression was applied to establish quantitative calibration analysis models. According to the prediction results, the combined near infrared and mid-infrared spectroscopy performed better than near infrared and mid-infrared models individually. The determination coefficient and root mean square error of prediction of astragaloside IV and total astragalosides were 0.998, 0.025 and 0.998, 0.098, respectively. It can be concluded that quantitative analysis models constructed by combined near infrared and mid-infrared spectroscopy had superior performance and could be used for rapid determination of main active components in Radix Astragali .